Penerapan Kemasan Aktif dan Sekunder pada Keripik Buah di UMKM Darsa Lampung Timur - Rahmadi, Isnaini; Nasution, Syahrizal; Mareta, Dea Tio (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M), Institut Teknologi Sumatera, Lampung, Indonesia., 2022)
MSMEs Darsa is a firm that takes advantage of East Lampung's bountiful fruit. Vacuum fraying is used by these MSMEs to make fruit chips. However, in order to achieve a lengthy shelf life, these MSMEs face challenges in the packaging process. Fruit chips can sometimes suffer from quality deterioration, such as becoming less crispy after being stored. Therefore, the solution proposed is to transfer and apply packaging technology, namely silica gel as moisture absorbance. Furthermore, supplementary packaging was used to increase sales. This program begins with discussions with partners to the implementation of premium full printing and stand up zipper lock windows as primary packaging. Goodie bag was chosen as the secondary packaging and silica gel as the active packaging. The results include publications in the mass media; the absence of damaged products; increased shelf life; partners understand the application of active packaging; poster; and videos of activities.